Neutral urea-based receptors for phosphates: synthesis and spectrophotometric studies. Issue 44 (3rd November 2016) - Formica, Mauro; Fusi, Vieri; Giorgi, Luca; Piersanti, Giovanni; Retini, Michele; Zappia, Giovanni
Abstract: A series of five fluorescent ligands (L1 –L5 ) for anions were designed and synthesized. Urea, thiourea, and cyanoguanidine moieties were chosen as the binding groups, while 3, 5-bis(trifluoromethyl)phenyl, coumarin, and BODIPY were used as the chromophores. The cyanoguanidinesL3 –L5 were promptly synthesized from corresponding thioureas using EDCI followed by reaction with cyanamide in the presence of triethylamine. The absorption and emission properties of the ligandsL1 –L5 were studied in CH3 CN; their coordination properties towards phosphate, pyrophosphate, and hydroxide anions, together with binding constants were evaluated. Graphical abstract: